2021
DOI: 10.3390/jmmp5010005
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Thin Walls with Sharp Corners in SS316L and IN718 Alloys Manufactured with Laser Metal Deposition

Abstract: In this work, the manufacture of thin walls with sharp corners has been optimized by adjusting the limits of a 3-axis cartesian kinematics through data recorded and analyzed off-line, such as axis speed, acceleration and the positioning of the X and Y axes. The study was carried out with two powder materials (SS316L and IN718) using the directed energy deposition process with laser. Thin walls were obtained with 1 mm thickness and only one bead per layer and straight/sharp corners at 90°. After adjusting the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…8, b) with a reported mass of seven kilograms. It indicates that the prepared design in PIGs shows good progress in cleaning the pipelines correctly [27]. On the other hand, the inline inspection MFL tool confirmed that it can safely pass through the known geometry anomaly inside the pipeline, as shown in Fig.…”
Section: Inline Inspection Resultsmentioning
confidence: 77%
“…8, b) with a reported mass of seven kilograms. It indicates that the prepared design in PIGs shows good progress in cleaning the pipelines correctly [27]. On the other hand, the inline inspection MFL tool confirmed that it can safely pass through the known geometry anomaly inside the pipeline, as shown in Fig.…”
Section: Inline Inspection Resultsmentioning
confidence: 77%
“…Several key AM technologies are applied with DED (directed energy deposition) and LPBF (Laser Powder Bed Fusion) processes. The first category is preferred for larger volumes or for repairing existing components [10][11][12][13][14][15][16][17]. LPBF is nevertheless the most widely used for aerospace applications where high density or shape complexity are required [18][19][20][21].…”
Section: Additive Manufacturing In the Aerospace Sectormentioning
confidence: 99%
“…Especially for the thin-wall parts, knowledge about the correlations between processing parameters and the final result is indispensable. [3], [4] This study explores the relation between the process parameter affecting the quality and properties of a series of AISI3016L stainless steel thin-walled parts produced by LMD. A six-axis robot was used with a deposition head that allows relative spatial movement between the powder nozzle and laser beam and substrate with high accuracy.…”
Section: Introductionmentioning
confidence: 99%